Examination of cytotoxic and antimicrobial effect of whitening toothpastes: an in vitro study - Numan Aydın; Aysun Kılıç Süloğlu; Neslihan İdil; Selen Öztürk; Serpil Karaoğlanoğlu (Medical Journals Sweden, 2024)
Objective: Toothpastes are widely used to protect oral and teeth health. This study aims to examine the cytotoxic and antimicrobial effects of whitening toothpastes. Methods: In this study, extracts were prepared according to ISO 10993-12:2021 standard (0.2 g/mL) using whitening and conventional toothpastes. The prepared extracts were added to human gingival fibroblast cell lines (HGF-1) in different dilutions (1:1, 1:2, 1:4, 1:8, 1:16, and 1:32) and a cytotoxicity test was performed. Antimicrobial analysis of toothpastes was performed on Streptococcus mutans, Staphylococcus aureus, and Candida albicans using the hole-plate diffusion method. Cell viability and microbial analysis data were examined using two-way analysis of variance (ANOVA) and Tukey post-hoc test (p < 0.05). Results: Toothpastes with sodium lauryl sulfate (SLS) in their composition showed statistically more toxic effects (p < 0.05). The activated carbon toothpastes without SLS showed over 90% cell viability after dilution. Although the dilution rate of toothpastes containing SLS increased, cell viability remained below 70%. All toothpastes used in the study showed antimicrobial effects on S. mutans, S. aureus, and C. albicans. Toothpaste containing hydrogen peroxide and SLS produced more antibacterial effects than activated carbon, blue covarine, microparticles, and conventional toothpaste. Conclusions: SLS-containing toothpastes showed more toxicity on HGF-1 cells. Toothpaste containing hydroxyapatite did not show toxic effects on HGF-1 cells. SLS, sodium lauryl sarcosinate and hydrogen peroxide in toothpastes increase antimicrobial effects.